The Role of Ethical Ideology in Reactions to Injustice - Hastings, Stephanie E.; Finegan, Joan E. (2011)
Forsyth (J Pers Soc Psychol 39(1):175–184, 1980) argued that ethical ideology includes the two orthogonal dimensions of relativism and idealism. Relativists determine morality by looking at the complexities of the situation rather than relying on universal moral rules, while idealists believe that positive consequences can always be obtained without harming others. This study examined the role of ethical ideology as a moderator between justice and constructive and deviant reactions to injustice. Students with work experience (N = 200) completed Bennett and Robinson’s (J Appl Psychol 85(3):349–360, 2000) measure of Workplace Deviance, Gill’s (Reactions to injustice: Development and validation of a measure. Unpublished doctoral dissertation, University of Western Ontario, 2005) Reactions to Injustice measure, and the Ethics Position Questionnaire (Forsyth, 1980), and provided ratings of justice in their own workplace. Hierarchical regressions revealed a significant main effect of idealism on deviance and constructive behaviors, and three-way interactions between idealism, relativism, and some types of justice. These findings suggest that ethical ideology plays a significant role in predicting responses to injustice.
Keywords: workplace deviance; Relativism; Organizational Justice; Idealism; Ethical Ideology; constructive reactions to injustice